Embroidered poetryAesthetics of writing poems (مجلة إحالات, 2026)
The current study sheds light on ancient Arabic poetry on embroidery, and it aims to identify theindividuals who carried out this process, while revealing the most important pillars on which the poetry wasembroidered. As well as to determine the most important contents of the embroidered poetry. The study concluded that some poetic lines and passages were written by lovers on fabrics and clothes of all kinds, as well as on curtains and handkerchiefs, to express their feelings of love and longing.